KADAR BIKARBONAT SALIVA PENDERITA KARIES DAN BEBAS KARIES - Arief Suryadinata (SAINSTIS, 2011)
Saliva plays a role as a buffer so that the ups and downs of the degree of acidity (pH) can be retained. salivary buffer capacity is determined by the bicarbonate concentration of 85%, 14% is determined by the concentration of phosphate and 1% by salivary proteins. Bicarbonate is the main component of saliva to neutralize the acid thus inhibiting the caries process. Based on the role of  bicarbonate in maintaining the pH of saliva to remain normal, there may be differences in levels of salivary bicarbonate in subjects  with caries and caries-free. This is because subjects with dental caries have the potential for acid formation and a decrease in pH higher than subjects with caries-free. This study aims to determine differences in levels of salivary bicarbonate in subjects  with caries and caries-free, studies are observational analytic study. Based on the result showed average levels of bicarbonate in the saliva of caries-free sample is 188.9440 ± 7.11846 ppm while in samples with high caries intensity is 150.9905 ± 9.76628 ppm, then the results of Kolmogorov-Smirnov normality test p-value of 0.200 obtained (p 0.05) in the sample with high intensity of caries and caries-free sample group. The results of the statistical test T-test two sample unpaired in getting the value of p = 0.000 (p 0.05), This means there are significant differences between the levels of salivary bicarbonate in subject with caries and caries-free.